Inkjet etching of micro-via holes in thin polymer layers - Yan Zhang (2014)
Facilitated by the development of various direct-write techniques and functional polymeric materials including polymer based conductors and semiconductors, printed electronics are flourishing both commercially and as a research topic. This is not only because of their simpler manufacturing routes and lower cost, but also as a result of lower processing temperatures and better compatibility with flexible substrates, compared with conventional electronics. The development of conventional electronics has been guided by Moore s Law, the driver for which lies in the demand for electronic devices with better performance and portability at lower prices. Therefore, one can expect a similar trend for printed electronics to guide its development. Multi-layered printing can be adopted in printed electronics to achieve higher density integration, so that this development trend can be maintained. In such circumstances, creation of electrical connections between multiple layers emerges as an important issue for printed electronics. Inkjet-etched via holes are one potential solution to providing such electrical interconnections, and which can provide good integration with other inkjet-printed features simply by switching nozzles. This thesis aims to elicit a better understanding of the physics involved in inkjet etching and investigate the capability of the inkjet etching technique. In the thesis, the factors that can affect the size of via holes produced by inkjet etching are evaluated, which is significant for evaluating the capability of this technique to deliver industrially relevant features. Identified factors include droplet ejection frequency, droplet diameter, solvent properties and substrate temperature. Droplet ejection frequency, i.e. the reciprocal of the time interval between drops, determines the extent of evaporation of the solvent between two consecutive drop impacts. Droplet diameter determines the radius of the wetted area after the droplet I impacts on the surface and spreads into a sessile drop. Solvents with different evaporation properties result in different size evolution with the number of drops dispensed, as does droplet ejection frequency. Higher substrate temperatures can reduce the drop diameter during flight and decrease the evaporation time on polymer surfaces, which can shrink the size of via holes. Another important issue is achieving complete polymer penetration as residual polymer creates an electrical conduction barrier after such holes are subsequently filled with conductive materials or act as a barrier to filling by electroplating. Experiments have been carried out to test the effect of outer diameter and polymer thickness on polymer penetration. Electroplating is utilised to test the completeness of via hole penetration. A mechanism using the Marangoni effect to explain the protrusion drying pattern other than a hole in the polymer layer is proposed.